SUSTANABILITY IN INFRASTRUCTURE PROJECT FINANCE: BINA ISTRA CASE - Silić, Dario; Silic, Ivana; Oberhofer Dimitrijevic, Gal (Global journal of Business and Integral Security, 2022)
Sustainability in infrastructure project finance is an important topic that has gained high importance in last decade. This became very important mainly as money providers in form of bank loans, equity or bonds require companies to comply with equator principles as condition precedent to financial close. Lenders, investment funds and other funding providers have in their prospectus, constitution acts or other corporate documents a clear condition related to sustainable development compliance or conditions from companies looking for finance. On top of that the laws or bylaws in many countries provide for many subsidies, tax reliefs or other incentives used by companies to get cheaper or more flexible financing. This is very much used in EU, USA and developed countries. How to achieve sustainable goals through project finance is one of the key concerns for many companies. Investments in sustainable development exist in many countries but further research is needed to better reposition the role and the future of sustainability in infrastructure project finance within boundaries and based on a concrete example of Bina Istra, the concessionaire of Istrian Epsilon motorway project in Istria, Croatia. Recent investments in sustainable development and future projects of Bina Istra as one of the biggest investor in construction of motorways in Croatia and region demonstrate that Lenders and money providers accept the financing of such big and challenging infra projects which propose a set of investments in sustainable development, mainly in reduction of pollution and energy optimization.